Successful remission induction with a combination therapy of rituximab, cyclophosphamide, and steroids in a patient with refractory optic neuritis in Wegener's granulomatosis - Huchzermeyer, Cord; Mardin, Christian Y.; Holbach, Leonard; Zwerina, Jochen; Schett, Georg; Rech, Juergen (Clinical Rheumatology, 2013)
A 56-year old patient with a history of limited Wegener's granulomatosis presented with signs and symptoms of optic neuritis. Radiologic signs of orbital inflammation were absent. Testing of visual acuity and visual field allowed close monitoring of disease activity. Thus, rapid improvement of visual function was achieved with high-dose steroids. Despite maintenance therapy with cyclophosphamide recurrence occurred repeatedly as soon as tapering of steroids was begun. After remission induction with rituximab, the patient retained good visual function under maintenance therapy with azathioprine and low-dose corticosteroids. Optic neuritis in Wegener's granulomatosis without signs of orbital involvement is rare and most likely caused by occlusive vasculitis of the vasa nervorum. In this patient with optic neuritis refractory to conventional therapy, rituximab in combination with cyclophosphamide and corticosteroids was well tolerated and successfully used for remission induction, followed by maintenance therapy with azathioprine and low dose corticosteroids.
EVALuna2:12699